Retrospective Study of Hyponatremia in Gastric Cancer Patients Treated with a Combination Chemotherapy of 5-Fluorouracil and Cisplatin: a Possible Warning Sign of Severe Hematological Toxicities? - Boku, N. (Japanese journal of clinical oncology, 2001)
Some anti-neoplastic agents induce hyponatremia. The relationship between hyponatremia and other toxicities in gastric cancer patients treated with 5-fluorouracil and cisplatin (FP) was investigated retrospectively to clarify its clinical significance. The subjects were 50 advanced gastric cancer patients treated with FP. Patients' performance status, oral intake, nausea/vomiting, diarrhea, fever, urine volume, presence of ascites or pleural effusion, laboratory data and administration of diuretics, corticosteroid and contents and volume of hydration before and during the first 5 days after chemotherapy were reviewed. The serum sodium level decreased after initiation of chemotherapy in all patients and the lowest level (nadir) was most frequently observed on day 8 (range, days 2-14), which preceded hematological toxicities. In 10 patients (20%) the nadir of serum sodium was lower than 125 mEq/l. We classified these 10 patients as a low-sodium group and the others into a normal-sodium group. Six (60%) and seven (70%) of the 10 patients in the low-sodium group had complications with grade 3 or 4 leukopenia and thrombocytopenia, whereas only one (3%) and two (5%) were seen in the normal-sodium group (p < 0.0001). Stomatitis and diarrhea were also slightly more severe in the former than the latter group. With respect to sensitivity and probability, receiver operating characteristic curves showed the nadir ((> or = ) or <125 mEq/l) of the serum sodium level was the best marker for both leukopenia and thrombocytopenia. Hyponatremia after initiation of chemotherapy with FP may be a warning sign of subsequent severe hematological toxicity.